Respostas

2013-11-14T16:19:32-02:00
( x - 5 ) + ( 2 x - 9 ) + ( 3 x - 13 ) + ( 4 x - 3 ) = 90                1) 12 - 5 = 7
x - 5 + 2 x - 9  + 3 x - 13 + 4 x - 3 = 90                               2) 2 . 12 - 9 =
x + 2 x + 3 x + 4 x = 90 + 5 + 9 + 13 + 3                               24 - 9 = 15
10 x = 120                                                                        3) 3 . 12 - 13 =
   x = 120 : 10                                                                       36 - 13 = 23
   x = 12                                                                            4) 4 . 12 - 3= 
                                                                                            48 - 3 = 45
O maior é  4 x - 3 que é igual a 45.
1 5 1
Bateu com a minha conta \o/ Obrigada!